Setting of operating patterns of crossing transportation on the sei Selari-Air Putih route in Riau province - Surnata, Surnata; Widjatmoko, Eko Nugroho; Yulianto, Andri; Latuheru, Paulina M.; Firzatullah, Raden Muhamad; Utami, Fisca Dian; Steven, Laurensius (Edelweiss Applied Science and Technology, 2024)
Sei Selari Ferry Port is a port located in Riau Province that serves the Sei Selari-Air Putih Passage. Load Factor at Sei Selari Ferry Port has reached the maximum limit so research is needed to improve the quality of service and safety of crossing transportation service users. The methods used in this research are Load Factor analysis, analysis of the suitability of minimum service standards for ship operations, analysis of ship requirements, and scheduling analysis. The technique used in this research is the saturated sampling technique because it uses the entire population (ship) as a research sample. Based on the results of the Load Factor calculation analysis, the average Load Factor of passengers and vehicles is 10% and 98.5% and the minimum service standards for ship operations have not been met by not matching the ship's departure time with the available schedule. There are differences from the Existing conditions, which are obtained from the results of the analysis of ship requirements and optimal ship scheduling, causing a difference between the applicable operating pattern and the analysis plan. The analysis results are calculated based on the number of trips and the number of ships according to the needs of service users. There is a difference between the Existing conditions and the results of the analysis, where the ideal number of ships is in accordance with the needs but it is necessary to increase the number of ship trips to 27 trips/day according to the needs of service users.